Price convergence, reversal speed and purchasing power parity: Stylized facts for Brazilian cities - Elano Ferreira Arruda; Ivan Castelar; Daniel Barboza Guimar\~aes; Rafael Barros Barbosa (EconomiA, 2018)
This paper analyzes the price dynamics of Brazilian cities between 1995 and 2012 to identify stylized facts about price convergence, the reversal speed of deviations between relative prices and purchasing power parity (PPP). There is evidence of a strong reduction in the absolute dispersion of prices of Brazilian cities and in the variability of relative prices. The estimated half-life of deviations from PPP reversal proved to be lower than those found for cross country data and American cities. The results also indicate that the stationarity of the real exchange rate among the cities is rejected for all the series that presented a reversal speed to deviations from the PPP smaller than the average for each numerarie considered. It is argued that the evidence of price convergence associated with a process of slow reversal speed of deviations from the PPP have influence on the non-rejection of a unit root in the real exchange rate series for some cities, however, this fact does not constitute in itself evidence against the validity of the PPP.
Keywords: F31; R10; E31; 330; Price convergence; Purchasing power parity; Real exchange rate; Reversal speed